Peran Pengasuhan Dalam Membina Kedisiplinan Santriwati Di Asrama Putri Pondok Pesantren Modern Ar-Raudlatul Hasanah Medan - Nurasmanissa, Ahmad Sanusi Luqman, Nurmisda Ramayani (Khazanah : Journal of Islamic Studies, 2022)
This study to aims to Determine the Role of Parenting in Fostering the Discipline of Students in The Dormitory of the Ar-RaudlatulHasanah Medan Islamic Boarding School,. The Objectives of this research are as follows: to find out the role of parenting in the dormitory in overcoming discipline, to find out the obstacles and efforts to improve the discipline of female students at PondokPesantren Modern Ar-RaudlatulHasanah Medan. This research belongs to the type of descriptive qualitative research, meaning that the writer will try to describe the method of data collection derived from observation, interviewrs and documentation. Data analysis techniques used are data reduction analysis techniques, data presentation, data verification of drawing concludion. Research found that the role of parenting in fortering the discipline was as follow : being a corrector, being an inspiratory, being a motivator, being a guide. The obstacles in increasing the discipline of students toward discipline, the student’s awareness of discipline. The efforts made to overcome the constraints of implementering discipline are : collaboration between parents/ guardians and increasing coordinations between caregivers. The results of the Islamic Boarding School Ar-RaudlatulHasanah Medan so that female students can better apply the discipline that has been enforced.